Kemunduran Dan Perkembangan Politik Turki Uthmani - Djalil, Bisri (STAI Miftahul Ula Nganjuk, 2017)
Abstract: The Caliphs Rashidin era is a period where the expansion of Islam is increasing, this is followed by Daula Umayyad and Abbasid Daula. Furthermore, the Turkish Uthmani Empire replace The Daulah Abbasid with the breadth of his domain. Unfortunately during Uthmani Turkey is not a lot of developments in science are successfully obtained, not as much as during the Abbasid Daula. After the death of Sultan Sulayman al-Qanuni year 974 AH / 1566 AD As a huge kingdom, the Ottoman Turks gradually decline. Substitute Sultan Sulaiman al-Qanuni turned out to be more concerned with themselves, their morale even worse, so inevitably the Ottoman empire in decline. Sometimes the area is reduced due to losing the war, sometimes growing again, then decline again. This lasted until the XXI century. Mustafa Kemal Pasha was a brilliant military cadres in a career. With the concept, he wants to make Turkey a secular state that is no longer an empire. With all the efforts and the movement of his dreams come true. In 1924 the Republic of Turkey was proclaimed by Mustafa Kemal Pasha as President and as Prime Minister Ismet Inonu.